2018
DOI: 10.1007/s10886-018-0941-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Defensive Metabolites in Nudibranch Molluscs

Abstract: Many plants and animals store toxic or unpalatable compounds in tissues that are easily encountered by predators during attack. Defensive compounds can be produced de novo, or obtained from dietary sources and stored directly without selection or modification, or can be selectively sequestered or biotransformed. Storage strategies should be optimized to produce effective defence mechanisms but also prevent autotoxicity of the host. Nudibranch molluscs utilize a diverse range of chemical defences, and we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 51 publications
2
78
0
1
Order By: Relevance
“…For example, nudibranchs sequester toxic compounds, which have been biosynthesized by the gastropod or acquired from their prey. The toxins are concentrated in the anatomical space of their mantles, the most vulnerable portion of their soft, exposed bodies (5254). Bioaccumulation of secondary metabolites in invertebrates with less anatomical differentiation is also known to occur.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nudibranchs sequester toxic compounds, which have been biosynthesized by the gastropod or acquired from their prey. The toxins are concentrated in the anatomical space of their mantles, the most vulnerable portion of their soft, exposed bodies (5254). Bioaccumulation of secondary metabolites in invertebrates with less anatomical differentiation is also known to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The same study reports that Chromodoris splendida from Australia presents aplysulphurin (61) (Figure 8), probably from its diet, the demosponge Darwinella tango, together with gracilin metabolites, such as gracilin C 20, not found in the sponge. A recent study on 19 species of Chromodoridid nudibranchs from Australia, mentioned above, reported many diterpenoids, among other compounds, found in mantle and internal glands [154]. In that work, mixtures of compounds are described in Goniobranchus nudibranchs, containing spongian diterpenes, norditerpenes, and rearranged diterpenes.…”
Section: Tricyclic Diterpenoidsmentioning
confidence: 92%
“…Although a defensive role is highly probable, it remains to be further proved using sympatric predators [46,153]. Recently, a study on 19 species of Chromodorididae nudibranchs from Australia reported 72 compounds, including many bicyclic furanosesquiterpenoids, among others, found in mantle and internal glands [154]. In particular, Mexichromis festiva contains euryfuran and dendrolasin, while M. mariei only possesses euryfuran.…”
Section: Bicyclic Sesquiterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesquiterpenes are C‐15 terpenoids that are classed as secondary metabolites with an extensive range of biological properties such as antifeedant, antibacterial and antifungal activities. Sesquiterpenes have defensive roles in plants .…”
Section: Chemistrymentioning
confidence: 99%